A physiological manoeuvre to improve the positivity of the gastro-oesophageal reflux scintigraphic test - Braga, FJHN; Miranda, JRD; Arbex, M. A.; Haddad, J.; Ferro, S. Z.; de Oliveira, R. B.; Ferriolli, E. (Lippincott Williams & Wilkins, 2001)
One of the best examinations used routinely to detect gastro-oesophageal reflux (GOR) is scintigraphy and attempts are continuously being made to improve the performance of the test. We have tested a new manoeuvre to improve the results. Three hundred and twenty eight patients (190 males and 138 females, aged 1 month to 84 years, average 4.47 years) were studied after a 12 h fast period with 100 MBq of Tc-99(m)-Phytate, 50 ml volume, directly delivered into the stomach in a mixture of orange juice. All patients were strongly suspected of having GOR. Conventional acquisition was done for 20 min, at a rate of one frame every 20 s. in the middle of the examination, small children were put in the upright position and held there for a few seconds or released in a way that allowed movement; adults were asked to stand up and walk a few metres. The test was then continued for the remaining 10 min. The global index of positivity was 64.6% (76 positive cases in the first half of the examination and 134 positive cases only after the manoeuvre). The mean of GOR episodes observed in the positive cases without the manoeuvre was 0.5 per patient, significantly different from the mean of 1.59 noted after the manoeuvre (P<0.01). In 28 cases the manoeuvre increased either the intensity or the frequency of reflux previously detected without it. We believe that this manoeuvre should be performed in all scintigraphic tests aiming to detect GOR. In the present series, the manoeuvre increased the frequency of GOR episodes. ((C) 2001 Lippincott Williams & Wilkins)].
Keywords: positivity; gastro-oesophageal reflux; scintigraphic test